Implementation of Performance Allowance Reduction through Work Discipline on Employee Performance at the Department of Population and Civil Registration of Sumenep Regency - Kurniawati, Dina; Kurdi, Moh.; Furqani, Astri (PT. Riset Press International, 2023)
The role of human resources is always crucial in the journey of an organization, as they are expected to provide a positive boost to performance development, especially in relation to the reduction of allowances for employees. The Department of Population and Civil Registration of Sumenep Regency, which is involved in public services, particularly emphasizes adequate performance from its employees in serving the general public. This research was conducted at the Department of Population and Civil Registration of Sumenep Regency and aimed to determine: a) the employees' perception of the impact of performance allowance reduction on performance, b) the employees' perception of work discipline's impact on performance, c) the impact of performance allowance reduction on work discipline, and d) the employees' perception of the impact of Performance Allowance Reduction on performance through the mediating factor of work discipline. Partial Least Squares (PLS) was used as the data analysis technique in this research. The results of the study showed that Performance Allowance has a significant positive influence on Work Discipline, and Performance Allowance and Work Discipline have a significant positive influence on Employee Performance.